Factors that determine the facilitation of stakeholders in environmental management – some philosophicalhistorical thoughts with the Merafong area as example - Eeden, E. S. van; Brink, I. (2007)
In essence, the article covers some fundamental principles of stakeholdership within a democratic process of environmental management. An effort is also made to point out several historical features of stakeholdership within the Wonderfonteinspruit (WFS) Catchment in the Merafong study area. Both these facets in the discussion accentuate stakeholdership as being primary participants (especially organisations that are government directed) and secondary participants (especially non-governmental organisations) in which both groups can reflect sufficient historical evidence in this economic environment to identify them as either the injurers, the injured or the participants/interested parties. To meaningfully conclude the discussion of stakeholdership in environmental management, some international and philosophical models and perspectives were also utilised to obtain a broader holistic perspective of a meaningful long-term stakeholder partnership. These applications, as reflected against a less fruitful awareness of the environmental practices in the past, can be applied efficiently in future stakeholder discussions regarding the WFS area as part of an approach featuring environmental justice and environmental remediation, compensation and monitoring.
Keywords: Wonderfontein Spruit Catchment Area; Stakeholder Facilitation; Water; Merafong; Gold Mines; Environmental Pollution; Environmental Ethics; Ecosystem